Current Mapuche-Huilliche Discourse and Poetics: Generational Shift and Territorial Difference (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
The ethnic-cultural (re)naissance in Chile is currently undergoing an expansion as well as a diversification along lines of minority cultures and gender differentiations. Since the explosion onto the Chilean literary landscape, in 1989, of the bilingual poet Leonel Lienlaf Lienlaf, Mapuche-Huilliche writers have come into the spotlight of academia, State and popular culture critics. Among other current distinctions, a younger generation of huilliche poets are distinguishing themselves through a hybrid, reflexive, and literary expressiveness. In opposition to the poetry that is tied to indigenous cultural institutions, orality, and traditional rural forms of existence, these poets thrive and strive for a pluricultural and complex way of living and expressing themselves. This work explores a selection of poets and their individual circumstances in an attempt to delineate the differences, and profile a greater cultural change that is coming about in south Chile.
Keywords: minority cultures; Mapuche-Huilliche writers; cultural changes